ENTOMOPHAGES AND PATHOGENS OF HARMFUL INSECTS IN UNABI AGROCOENOSES AND THEIR SIGNIFICANCE IN THE ECOSYSTEM (Scientific journal of the Fergana State University, 2025)
This article provides information about the entomophages and pathogens of harmful insects in the unabi plant agrocoenosis and their significance.